Governance Characteristics and Tax Avoidance: Evidence from Indonesia - Anis Muviqotul Azizah; Sri Andriani (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Tax avoidance is a crucial issue in corporate governance and public finance as it directly affects government revenue and corporate legitimacy. Specific Background: In the energy and raw materials sector, tax avoidance is a growing concern due to the size of companies’ asset bases, the complexity of their operations, and their high social and environmental exposure, which makes internal governance factors highly relevant in explaining tax avoidance behaviour. Knowledge Gap: Previous research on tax avoidance in Indonesia has yielded mixed results, as most studies have analysed corporate characteristics in isolation and have not focused sufficiently on sector-specific conditions, particularly in the energy and raw materials sectors. Objective: This study examines the influence of corporate social responsibility (CSR), gender diversity and firm size on tax avoidance, both partially and simultaneously. Method: This study employs panel data regression analysis using secondary data sourced from the annual and sustainability reports of energy and raw materials companies listed on the Indonesia Stock Exchange for the years 2022–2024. Results: An R² value of 0.944 indicates that the research model is able to explain tax avoidance to a significant extent. Novelty: This study was conducted following the enactment of the HPP Act in Indonesia; given this issue, it is believed that more accurate information is required regarding the latest measures relating to tax avoidance. Implications: The findings can serve as input for various stakeholders, such as the government, companies and investors, in promoting more transparent tax practices and strengthening corporate governance.